2021
DOI: 10.3389/fpsyt.2021.736228
|View full text |Cite
|
Sign up to set email alerts
|

Eye Movements and Cognitive Functioning in Patients With Schizophrenia Spectrum Disorders: Network Analysis

Abstract: Background: Eye movement parameters are often used during cognitive functioning assessments of patients with psychotic spectrum disorders. It is interesting to compare these oculomotor parameters with cognitive functions, as assessed using psychometric cognitive tests. A network analysis is preferable for understanding complex systems; therefore, the aim of this study was to determine the multidimensional relationships that exist between oculomotor reactions and neurocognition in patients with schizophrenia sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The literature is scarce about the relationship between oculomotor impairment and a low processing speed. For example, a recent study found a low PSI in children with schizophrenia and oculomotor impairment [ 63 ]. Interestingly, lower PSI scores have been reported in many neurodevelopmental disorders, such as learning disabilities, ADHD, or high-functioning ASD [ 62 , 64 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…The literature is scarce about the relationship between oculomotor impairment and a low processing speed. For example, a recent study found a low PSI in children with schizophrenia and oculomotor impairment [ 63 ]. Interestingly, lower PSI scores have been reported in many neurodevelopmental disorders, such as learning disabilities, ADHD, or high-functioning ASD [ 62 , 64 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past three decades, eye movements have been used as an experimental screening tool to gain insight into AIDS-related diseases, learning-related disorders, psychiatric disorders, neuromuscular disorders, fetal alcohol spectrum disorders and neurological disease. (Bittencourt et al, 2013;Green et al, 2007;Jaafari et al, 2011;Nerušil et al, 2021;Shmukler et al, 2021). Due to the overlap between brain areas that mediate saccadic eye movement function and that which are injured by HIV persistence, specifically the basal ganglia and deep white matter (Boissé et al, 2008) saccadic eye movement testing may provide valuable insight into CNS of people diagnosed with HIV/AIDS.…”
Section: Eye Movement Studies In Different Disease Statesmentioning
confidence: 99%
“…Eye movement as a neurophysiological indicator, and associated with higher cognitive processes and psychomotor functions (25,26). Prosaccades are recognized as reflexive saccades, where participants need bottom-up attention to complete this paradigm (27), while antisaccades involve inhibition and cognitive control (28,29). These results strongly suggest a relationship between abnormal eye movements and cognitive deficits in schizophrenia.…”
Section: Introductionmentioning
confidence: 98%
“…These results strongly suggest a relationship between abnormal eye movements and cognitive deficits in schizophrenia. It has been shown that the directional error rate and antisaccade latency in patients with schizophrenia during the antisaccade tasks are related to performance on the Digit Sequencing and Symbol Coding Test, respectively ( 30 ). Higher cognitive processes involved sensorimotor and visual information switching abilities have been demonstrated in the antisaccade task ( 31 ).…”
Section: Introductionmentioning
confidence: 99%